2020
DOI: 10.53936/afjare.2020.15(1).02
|View full text |Cite
|
Sign up to set email alerts
|

Health and environmental effects of adopting an integrated fruit fly management strategy among mango farmers in Kenya

Abstract: Integrated pest management (IPM) has been promoted globally as an alternative approach to the widespread broad-spectrum chemical insecticidal application for the control of pests and diseases in agricultural production to minimise the harmful effects of the chemicals on humans and the environment. This study examines the impact of an IPM strategy developed to control mango fruit flies on humans and the environment. Using a random sample of 371 mango farmers from Meru County in Kenya, health and environmental o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The EIQ analysis using the reported insecticides in tomato production in Kenya and Uganda showed that farmers were using pesticides of EIQ ranging between high and moderate. The finding supports Mwungu et al (2020) who found that active chemicals present in mango production were lower than Field EIQ 40. The pesticides used in tomato production in Kenya and Uganda fall under Class II of the WHO pesticide classification, suggesting that they have a potentially adverse impact on the environment, consumers, and farmers.…”
Section: Discussionsupporting
confidence: 88%
“…The EIQ analysis using the reported insecticides in tomato production in Kenya and Uganda showed that farmers were using pesticides of EIQ ranging between high and moderate. The finding supports Mwungu et al (2020) who found that active chemicals present in mango production were lower than Field EIQ 40. The pesticides used in tomato production in Kenya and Uganda fall under Class II of the WHO pesticide classification, suggesting that they have a potentially adverse impact on the environment, consumers, and farmers.…”
Section: Discussionsupporting
confidence: 88%